Opening up the university : teaching and learning with refugees - Cantat, Céline; Cook, Ian M.; Rajaram, Prem Kumar (Higher Education in Critical Perspective: Practices and Policies Ser., 2022)
"Through a series of empirically and theoretically informed reflections, Opening Up the University offers insights into the process of setting up and running programs that cater to displaced students. Including contributions from educators, administrators, practitioners, and students, this expansive collected volume aims to inspire and question those who are considering creating their own interventions, speaking to policy makers and university administrators on specific points relating to the access and success of refugees in higher education, and suggests concrete avenues for further action within existing academic structures"--